Prolonged toilet training in children with Down syndrome: a case‐control study - Flávia Cristina de Carvalho Mrad; André Avarese de Figueiredo; José de Bessa Jr; José Murillo Bastos Netto (Brazilian Society of Pediatrics, 2018)
Objectives: Children with Down syndrome have delayed psychomotor development, which is a factor that influences the level of difficulty in toilet training. The current study aims to estimate the age toilet training starts and completes in children with DS compared to children with normal psychomotor development and to evaluate the method and type of toilet training most frequently used, as well as its association with lower urinary tract symptoms and functional constipation. Methods: A case‐control study was carried out from 2010 to 2015. All parents completed a questionnaire designed to assess the toilet training process. Lower urinary tract symptoms were assessed through the application of the Dysfunctional Voiding Symptom Score. The presence of functional constipation was assessed according to the Rome III criteria. Results: The study included 93 children with Down syndrome and 204 children with normal psychomotor development (control group [CG]). The mean age of toilet training onset was 22.8 months in those with DS and 17.5 months in the CG (p = 0.001). In children with DS, the mean age when completing toilet training was 56.2 months and 27.1 months in the CG (p = 0.001). Among children with DS, females completed toilet training earlier (p = 0.02). The toilet training method used most often was child‐oriented approach in both groups. No association was observed with the presence of lower urinary tract symptoms or functional constipation and the age of beginning and completing toilet training in both groups. Conclusion: Children with Down syndrome experienced prolonged toilet training time. Prospective longitudinal studies are essential to gain insight into the toilet training of these children. Resumo: Objetivos: Crianças com síndrome de Down apresentam desenvolvimento psicomotor atrasado, fator que influencia o nível de dificuldade do treinamento esfincteriano. O presente estudo tem como objetivo estimar a idade em que o treinamento esfincteriano é iniciado e concluído em crianças com SD em comparação com crianças com desenvolvimento psicomotor normal, avaliar o método e o tipo de treinamento esfincteriano utilizado com maior frequência, bem como sua associação com sintomas do trato urinário inferior e constipação funcional. Métodos: Um estudo caso‐controle foi realizado de 2010 a 2015. Todos os pais preencheram um questionário destinado a avaliar o processo de treinamento esfincteriano. O sintomas do trato urinário inferior foram avaliados por meio da aplicação do Dysfunctional Voiding Symptom Score. A presença de constipação funcional foi avaliada de acordo com os critérios Roma III. Resultados: O estudo incluiu 93 crianças com síndrome de Down e 204 crianças com desenvolvimento psicomotor normal (Grupo de Controle [GC]). A idade média em que as crianças iniciaram o treinamento esfincteriano foi de 22,8 meses naquelas com SD e 17,5 meses no GC (p = 0,001). Em crianças com SD, a idade média ao concluir o treinamento esfincteriano foi de 56,2 meses e 27,1 meses no GC (p = 0,001). Entre as crianças com SD, as do sexo feminino concluíram o treinamento esfincteriano mais cedo (p = 0,02). O método de treinamento esfincteriano mais utilizado foi a abordagem voltada para a criança em ambos os grupos. Não houve associação com a presença de sintomas do trato urinário inferior ou constipação funcional e a idade no início e na conclusão do treinamento esfincteriano em ambos os grupos. Conclusão: Crianças com síndrome de Down apresentaram tempo de treinamento esfincteriano prolongado. Estudos longitudinais prospectivos são essenciais para obter uma visão do treinamento esfincteriano dessas crianças. Keywords: Children, Down syndrome, Functional constipation, Lower urinary tract symptoms, Toilet Training, Palavras‐chave: Crianças, Síndrome de Down, Constipação funcional, Sintomas do trato urinário inferior, Treinamento esfincteriano